Removal Of Cobalt From Ammonium Chloride Solutions Using A Batch Cell Trough An Electrogenerative Process - Cheng, Chor Yee (2017)
An electrogenerative system is applied to remove cobalt from ammonium chloride solution. In this process, a chemical reaction takes place spontaneously where cobalt is reduced at the cathode compartment and zinc is oxidized at the anode compartment without the supply of external energy. The electrogenerative removal of cobalt was conducted in a batch reactor using a three-dimensional electrode: 80 pores per inch (ppi) reticulated vitreous carbon (RVC) as cathode material. Studies of removal of cobalt from ammonium chloride solution were accomplished using ammonium chloride as supporting electrolyte medium.